Language Use in Real‐Time Interactions During Early Elementary Science Lessons: The Bidirectional Dynamics of the Language Complexity of Teachers and Students. Issue 2 (22nd December 2016) - Menninga, Astrid; van Dijk, Marijn; Steenbeek, Henderien; van Geert, Paul
Abstract : This study used a dynamic approach to explore bidirectional sequential relations between the real‐time language use of teachers and students in naturalistic early elementary science lessons. It also compared experienced teachers ( n = 22) with novice teachers ( n = 8) with respect to such relations. Verbal interactions were transcribed and coded at the utterance level for syntactic complexity, lexical density of content word use, and open‐ended teacher questions. Sequential analyses provided evidence for the existence of a bidirectional relationship, meaning that both teachers and students were sensitive to each other's use of complex and dense language. In addition, the use of open‐ended teacher questions was related to complex and dense student utterances. Comparisons between experienced teachers and novice teachers revealed that sequential patterns were stronger in the case of experienced teachers, suggesting that there were more flexible adaptation processes in this group.